2019
DOI: 10.1044/2019_jslhr-l-18-0341
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Attention in Typically Developing Children and Children With Developmental Language Disorder

Abstract: Purpose The aim of the current study was to investigate whether dual language experience modulates the efficiency of the 3 attentional networks (alerting, orienting, and executive control) in typically developing (TD) children and in children with developmental language disorder (DLD). Method We examined the attentional networks in monolingual and bilingual school-aged children (ages 8–12 years) with and without DLD. TD children (35 monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…We feel that this finding is unlikely to be caused by insufficient power, given that our sample size was validated by previous work (Fernandez et al, 2019b). In addition, although the ANT has been successfully employed in several studies to assess major attentional components across various populations (Wang et al, 2005;Fernandez-Duque and Black, 2006;Mahoney et al, 2010;Park et al, 2019), it may have failed to capture another attentional dimension that is possibly affected by amusia. Nevertheless, the current finding of comparable visuospatial attentional performance in this paradigm, despite the congenital impairment associated with amusia, helps to further refine our understanding of this disorder.…”
Section: Effects Of Emotional Music On Attention In Amusiamentioning
confidence: 82%
“…We feel that this finding is unlikely to be caused by insufficient power, given that our sample size was validated by previous work (Fernandez et al, 2019b). In addition, although the ANT has been successfully employed in several studies to assess major attentional components across various populations (Wang et al, 2005;Fernandez-Duque and Black, 2006;Mahoney et al, 2010;Park et al, 2019), it may have failed to capture another attentional dimension that is possibly affected by amusia. Nevertheless, the current finding of comparable visuospatial attentional performance in this paradigm, despite the congenital impairment associated with amusia, helps to further refine our understanding of this disorder.…”
Section: Effects Of Emotional Music On Attention In Amusiamentioning
confidence: 82%
“…This study included sixty‐six 8–12‐year‐old children: 14 monolingual TD (MO‐TD), 12 bilingual TD (BI‐TD), 28 monolinguals with fDLD (MO‐fDLD) and 12 bilinguals with fDLD (BI‐fDLD). These children were a subset of a larger project investigating procedural learning (Park et al., 2018), attention (Park et al., 2019), processing speed (Park et al., 2020) and motor abilities (Sanjeevan and Mainela‐Arnold 2019). Age did not differ among the four groups (MO‐TD, BI‐TD, MO‐fDLD, BI‐fDLD), F (3, 62) = 0.82, p = 0.489.…”
Section: Methodsmentioning
confidence: 99%
“…The ANT is designed to measure three subcomponents of attention (alerting–vigilance, orienting–relocating attention and executive attention). We only included the executive attention measure because our prior study (Park et al., 2019) revealed that of the three subcomponents of attention, only executive attention results differed between the children with DLD and typical development across mono‐ and bilinguals. This parallels other studies reporting executive attention deficits in children with DLD (e.g., monolinguals: Pauls and Archibald 2016; and mono‐ and bilinguals: Ebert et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations